(untitled) (Research, Society and Development, 2021)
Green manuring and the spatial arrangement of planting intercropped crops are manageable factors to increase the bioeconomic effectiveness of intercropped systems. Therefore, the object of this study was to work out the bio-economic efficacy in cowpea-radish association under diverse Calotropis procera biomass amounts and planting arrangements in two cultivation seasons through biological and economic indices. The research was conducted in a design of randomized complete blocks with four repetitions. The treatments were made of combination of four C. procera biomass amounts placed into the soil (20, 35, 50 and 65 t ha-1) with three cowpea-radish planting arrangements (2:2, 3:3 and 4:4). The biological indices, land equivalent ratio (LER), area-time equivalency ratio (ATER), actual yield loss (AYL), and system productivity index (SPI) and the economic indicators gross revenue (GR), net revenue (NR), rate of return (RR) and profit margin (PM) were evaluated to express the bio-economic efficacy of the cowpea-radish association. The greatest biological efficiencies of the cowpea-radish association were attained with LER and ATER of 1.75 and 1.25; AYL and SPI of 1.48 and 13.15 t ha-1, respectively, in the amount of 62 t ha-1 of C. procera biomass in the planting arrangements 2: 2 and 3: 3. The largest net economic revenue (NR) of 16,382.85 R ha-1 was attained in the amount of 52 t ha-1 of C. procera in the planting arrangement 3: 3.